NETosis‐associated serum biomarkers are reduced in type 1 diabetes in association with neutrophil count. (13th April 2016) - Qin, J.; Fu, S.; Speake, C.; Greenbaum, C. J.; Odegard, J. M.
Summary: As the immune pathways involved in the pathogenesis of type 1 diabetes (T1D) are not fully understood, biomarkers implicating novel mechanisms of disease are of great interest and call for independent evaluation. Recently, it was reported that individuals with T1D display dramatic elevations in circulating components of neutrophil extracellular traps (NETs), indicating a potential role for NETosis in T1D. Our aim was to evaluate further the potential of NET‐associated proteins as novel circulating biomarkers in T1D. We tested serum from subjects with T1D ( n = 44) with a median age of 26·5 years and a median duration of 2·2 years, along with 38 age‐matched controls. T1D subjects did not show elevations in either neutrophil elastase (NE) or proteinase 3 (PR3), as reported previously. In fact, both NE and PR3 levels were reduced significantly in T1D subjects, particularly in subjects within 3 years of diagnosis, consistent with the known reduction in neutrophil counts in recent‐onset T1D. Indeed, levels of both NE and PR3 correlated with absolute neutrophil counts. Therefore, while not ruling out potential local or transient spikes in NETosis activity, the levels of these serum markers do not support a role for systemically elevated NETosis in the T1D population we studied. Rather, a modest reduction in these markers may reflect other important aspects of disease activity associated with reduced neutrophil numbers.